Adapting biophilic design in urban riparian - Omar, Siti Rahmah; Sohaili, Johan; Abd Rahman, Nur Hidayah (SingEx Exhibitions Pte. Ltd., 2018)
The global rapid urbanization has had significant impacts on the environmental quality. As with many other countries, Malaysia has not been spared from this issue. The unprecedented urban growth has occurred at the expense of many green spaces and vegetation which promote ecosystem and human health. Urban riparian is one of the greenery commonly unaffected by the urban expansion. It has vital ecosystem functions, including maintaining the river water quality, conserving the biodiversity, and stabilizing the river banks. As such, creating a conducive urban riparian zone becomes an important strategy to promote the development of biophilic cities. This study, therefore, aimed to determine the potential functions of the urban riparian to the adjacent occupants by adopting the biophilic design approaches. To achieve the objective, two forms of river reserves were investigated by comparing a vacant riparian area in its natural condition with a riparian area that has been upgraded into a fully-utilized green space. The study observed a lack of spatial integration between the green space and the built-up area in the neglected and unmanaged riparian. On the contrary, the upgraded riparian area was more popular among the public, demonstrating a positive sense of connection between the people and the site. Moreover, the upgraded area was shown to have a lower thermal condition and a better ventilation, hence having the potential to improve the living conditions of the developed area. In conclusion, the study established that there are multiple functions of the urban riparian, especially after implementing the biophilic design approaches within the area.